Optimasi Pelayanan Kesehatan Balita Melalui Posyandu Merpati Di Desa Kalensari Compreng - Ira Hamidatul Apiah; Imron Fathurohman; Septian Eka Prahardik; Ahmad Farihin (CV. ITTC INDONESIA, 2024)
This research delineates the significant role of Posyandu in improving toddler health in Kotasari Hamlet, Kalensari Village. Through structured monthly activities, Posyandu effectively monitors the development of 12 toddlers consistently. Despite occasional attendance surpassing expectations, the study concludes that Posyandu holds a pivotal role in enhancing toddler health. Routine activities, including registration, data collection, weight measurement, height assessment, and growth recording in the KMS book, are consistently conducted. Posyandu also provides immunizations, health education, and basic care for pregnant women. Collaboration with local health centers and non-governmental organizations expands access to healthcare, including training healthcare personnel and procuring medical equipment. The primary focus on toddler health involves providing nutrition, immunizations, and growth monitoring. The holistic nutrition education program and timely immunizations serve as significant preventive measures. Regular monitoring, including weight measurements, height assessments, and growth data recording, forms the basis for early identification of health issues. Consequently, Posyandu in Kotasari Hamlet is not just a physical health center but also a platform for education and stimulation of child development, supporting optimal health and growth for toddlers in the region. The method applied in this community service program is socialization, aimed at delving deeper through a participatory and interactive approach. This socialization method encompasses various educational activities, community meetings, and the utilization of information technology as an effective means of conveying information to the public.